Airway surface liquid homeostasis in cystic fibrosis: pathophysiology and therapeutic targets. Issue 3 (30th December 2015) - Haq, Iram J; Gray, Michael A; Garnett, James P; Ward, Christopher; Brodlie, Malcolm
Abstract : Cystic fibrosis (CF) is a life-limiting disease characterised by recurrent respiratory infections, inflammation and lung damage. The volume and composition of the airway surface liquid (ASL) are important in maintaining ciliary function, mucociliary clearance and antimicrobial properties of the airway. In CF, these homeostatic mechanisms are impaired, leading to a dehydrated and acidic ASL. ASL volume depletion in CF is secondary to defective anion transport by the abnormal cystic fibrosis transmembrane conductance regulator protein (CFTR). Abnormal CFTR mediated bicarbonate transport creates an unfavourable, acidic environment, which impairs antimicrobial function and alters mucus properties and clearance. These disease mechanisms create a disordered airway milieu, consisting of thick mucopurulent secretions and chronic bacterial infection. In addition to CFTR, there are additional ion channels and transporters in the apical airway epithelium that play a role in maintaining ASL homeostasis. These include the epithelial sodium channel (ENaC), the solute carrier 26A (SLC26A) family of anion exchangers, and calcium-activated chloride channels. In this review we discuss how the ASL is abnormal in CF and how targeting these alternative channels and transporters could provide an attractive therapeutic strategy to correct the underlying ASL abnormalities evident in CF.